NHC Adducts of Disilylated Germylenes and Stannylenes and Their Coordination Chemistry with Group 11 Metals. Issue 22 (28th October 2016) - Walewska, Małgorzata; Hlina, Johann; Gaderbauer, Walter; Wagner, Harald; Baumgartner, Judith; Marschner, Christoph
Abstract : Syntheses of NHC adducts of bis[tris(trimethylsilyl)silyl]germylene and ‐stannylene and some structurally related cyclic disilylated stannylenes are reported. Reactions of a cyclic stannylene NHC adduct with gold and silver cyanide led to cationic metal complexes with two cyanostannyl ligands. The Ag complex decomposed further to a cyanostannide. Reactions of bis[tris(trimethylsilyl)silyl]germylene and ‐stannylene NHC adducts with gold and silver cyanide displayed more unusual coordination chemistry with one silyl group of the ylene unit being transferred to the group 11 metal. Abstract :